Konfusianisme dalam Kebudayaan Cina Modern - Hartati, Dewi (Paradigma: Jurnal Kajian Budaya, 2012)
Confucianism aims to educate and emphasize for people to serve the state and society. To understand Confucianism is necessary to understand the book of Daxue 大学 (Great Teaching), which contains teachings on ethics, the ethics of family, society and state. Confucianism is not an ideology at the state level or national level but rather to a personal level. Confucianism, which emphasizes self-processing in a personal level is what can survive for so long and respected, and spread to all levels and persists in the modern world.